Antenatal Diagnosis of a Giant Fetal Hepatic Hemangioma and Treatment with Maternal Corticosteroid - Schmitz, R.; Heinig, J.; Klockenbusch, W.; Kiesel, L.; Steinhard, J. (Ultraschall in der Medizin - European Journal of Ultrasound, 2009)
Initial diagnosis of a fetal hemangioendothelioma of the liver was made at 28 + 1 weeks of gestation. Due to the growth of the liver tumor and increasing fetal cardiac load, 4 mg dexamethasone were administered daily from 32 + 3 to 36 + 6 weeks of gestation. With this medication the fetal cardiac load was unchanged and slow further increase of the tumor size occurred. At 36 + 6 weeks of gestation, a primary caesarean section was performed due to fetal heart decompensation and pathological CTG. Maternal therapy with dexamethasone should be considered for antenatally detected Giant Fetal Hepatic Hemangioma.
Keywords: fetus; hemangioma; obstetrics; pregnancy; 3 D ultrasound